Sitotoksisitas pemutih gigi berdasarkan konsentrasi bahan - Mardiana A. Adam; Asti Meizarini (Journal of Dentomaxillofacial Science, 2010)
The aim of this study was to evaluate the cytotoxicity of several tooth whitening material,carbamide peroxide 10%, 15%, 20% and hydrogen peroxide 38% toward BHK-21 cellusing MTT assay. Each well of microplates which used for the test were aliquotted BHK21cell suspension, after that the test solution were added to eight well each group,respectively. The result showed that percentages of the living cell at 10% carbamideperoxide group = 86,73%; 15% = 81,22%; 20% = 81,82%; 38% hidrogen peroksida =64,08%, respectively. Anova test and LSD showed no significant difference between 10%,15%, 20% groups, but there are significant toward 38% group and control. The 38%hydrogen peroxide group is expectable to be more cytotoxic than those containing 10%carbamide peroxide, which is equivalent to 3.6% hidrogen peroxide. Conclusion.The10%, 15%, 20 % carbamide peroxide and 38% hydrogen peroxide tooth whiteningagents were not cytotoxic toward BHK-21 cell line using MTT assay within CD